Connectivity and management of technological supplies in educational institutions during COVID 19 - Rojas Torres, Estephany Abigail (2022)
A documentary review was carried out on the production and publication of research papers related to the study of the variable Connectivity and Management of Technological Supplies in Educational Institutions during Covid-19 in Latin America. The purpose of the bibliometric analysis proposed in this document is to know the main characteristics of the volume of publications registered in Scopus database during theperiod between 2020 and the first semester of 2021 in Latin American countries, achieving the identification of 32 publications in total. The information provided by this platform was organized by means of graphs and figures, categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics were described, the position of different authors regarding the proposed topic was referenced by means of a qualitative analysis. Among the main findings of this research, it is found that Mexico, with 10 publications, is the Latin American country with the highest production. The area of knowledge that made the greatest contribution to the construction of bibliographic material related to the study of Connectivity and Supply Management was Social Sciences with 19 published documents, and the type of publication that was mostused during the period mentioned above was the journal article, which represents 66% of the total scientific production.